Uji Validitas dan Reliabilitas Kuesioner Skrining Kaki Diabetik - Supriyadi Supriyadi; Novita Dewi (Universitas Baiturrahim, 2023)
Ulceration of the foot in diabetes is common and disabling. It frequently leads to leg amputation, and the risk for leg amputation increases 10 to 30 times higher among the general population. 85% of leg amputations are performed due to diabetic foot ulcers, which can affect the quality of life and be potentially life-threatening. Diabetic foot ulcers are preventable by performing foot screening. The study aims to determine the validity and reliability score of diabetic foot screening questionnaires. The study used an observational descriptive design with a cross-sectional approach to the samples of 35 out of 40 populations. Respondents are selected using simple random sampling techniques. The instrument used was the diabetic foot ulcer and blood sugar observation sheet. The data were tested using SPSS 26 using Pearson Product Moment and Cronbach's Alpha test. The majority of respondents were female, the age ratio of the respondents was 65 years, the blood sugar rate was 234 mg/dl, and the ankle-brachial index rate was 1.04. The Pearson Product Moment results showed that the rcounts > rtable (0.334), while the reliability test using Cronbach’s Alpha value is > 0.60. The diabetic foot screening questionnaire is declared valid, reliable, and appropriate to detect the risk of foot ulcers in patients with Type 2 Diabetes Mellitus. There are ten themes of questions: diabetic diet patterns, anti-diabetic medication consumption, monofilament tests, foot pulse, history of foot ulcers, a history of amputations, foot deformities, nails growing into tissue, callus, and cracks.